Use Of Glutathione As An Additional Supplement For The Treatment Of Fatty Liver Disease : A Systematic Review - Pretty Grace Zalukhu; Widjaja Lukito (International Medical Journal Corp. Ltd, 2024)
Introduction : The liver normally contains fat tissue, but if it exceeds 5% of the liver weight, this condition is called fatty liver disease. Fatty liver disease is divided into two major groups, namely : Alcoholic Fatty Liver Disease (AFLD) and Non-Alcoholic Fatty Liver Disease (NAFLD). Fatty liver disease can potentially progress to liver cirrhosis, and this can be prevented by antioxidants, through their anti-inflammatory actions. Glutathione is a potent antioxidant, and naturally produced in our body, with the highest level in the liver, which is the main organ in the detoxification process. This study aimed to systematically review the importance of Glutathione as an adjunct supplement for the treatment of fatty liver disease, which is one of antioxidants, can help with fatty liver problems. Methods : This study applied a Systematic Review approach, that included published articles with Randomized Controlled Trials (RCTs). We searched these articles in two electronic databases, namely Google Scholar and PubMed. Based on the search, 1.141 cases of fatty liver were found and the author determined 2 (two) relevant literature/studies that focus on this research. Results : Based on 2 studies with a total of 208 patients and divided into 2 groups, namely the intervention group and the control group, it was found that the group that was intervened with glutathione supplementation for at least 3 months experienced a decrease in CAP, ALT, and IMT values. Especially if coupled with MHD/improved healthy lifestyle, the recovery process of fatty liver conditions can take place faster. Conclusions : Glutathione as an antioxidant and acts as a hepatoprotector, demonstrated the ability to potentially hold the progression of NAFLD, and improve liver function. The presence of MHD/improve healthy lifestyle synergized the efficacy of Glutathione against the progression of NAFLD.